THE IMPACT OF GENERAL AIR CRYOTHERAPY ON OXYGEN TRANSPORTING FUNCTION OF THE PATIENTS’ BLOOD WITH METABOLIC SYNDROME - N. V. Hodarev; N. L. Ghemchyghnova; E. V. Olempieva; A. N. Sokolov; S. G. Nechin (Медицинский вестник Юга России, 2015)
Purpose: studying of the impact of the general air cryotherapy on oxygen transporting function of the patients’ blood with metabolic syndrome.Materials and Мethods: 70 patients are included, average age is 45,3Ѓ}3,7 years. The analysis of the indicants of gas transporting function of the patients’ blood with metabolic syndrome before and after the general air cryotherapy course was carried on.Results: patients with metabolic syndrome revealed the presence of quantitative and modulation adaptation type oxygen transporting blood function and the formation of compensatory-adaptive reactions that support the processes of dissociation of oxyhemoglobin. After a full course of general air creotherapy treatments the clinical group patients are noticed to have the restructuring of oxygen metabolism in the form of a reduction in the tissue hypoxia intensity and enhance of the erythrocytes’ aerobic metabolism processes.Summary: the obtained results allow to recommend this method of physiotherapeutic effect for patients with metabolic syndrome with the aim to increase endurance and resistance levels towards hypoxic factor in low temperatures conditions.